Strategy Approach for the Development of a Sustainable Environmentally Friendly Tourism City - SULISTYOWATI, Lilik; KRISNAWATI, Eny; ANDARESWARI, Novi; AFRIANTO, Firman; RAIS, Abdul; HAFA, Mohammad Fauzi; DARWIYATI, Darwiyati; GINTING, Andi Lopa; HIDAYATULLAH, Rifqi Rahmat (Journal of Environmental Management and Tourism, 2024)
This study employs a case study approach in the Batu City Region, East Java Province, Indonesia. Over time, Batu City has undergone a significant transformation, particularly in the tourism sector, leading to the growth of a large service industry. This study aims to propose a comprehensive development strategy for the Batu City area integrating economic, social, and environmental elements into the spatial layout of Batu City, with the ultimate goal of establishing an environmentally friendly Tourism City. Strengths, weaknesses, opportunities, threats analysis and analytic hierarchy process were employed to assess data from interviews, questionnaires, and agency sources. The stages of analysis are as follows: 1) data collection, 2) analysis, and 3) strategic prioritizing. This study recommends the main priority strategy for the development of a sustainable environmentally friendly tourism city is committing to implementing the principles of sustainable urban development and environmentally friendly tourism citiy through Regional Regulations. Considering the unique attributes of each city, such us their economy, resources, policies, and environment, among other factors, this paper considers contextual relevance issues. By doing so, it assists cities in developing sustainable cities based on their own strengths, weaknesses, opportunities, and threats.